THE HEMOSTATIC ACTIVITY OF BIS (2-AMINOETHAN-1-SULFONATE) CALCIUM - Gurevich, Konstantin G; L Urakov, Aleksandr; I Bashirova, Linara; V Samorodov, Aleksandr; P Purygin, Peter; A Yermokhin, Vladimir; S Gilmutdinova, Alfiya; A Bondareva, Nataliia (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: It is known that local or systemic injection of hemostatic drugs is used to reduce blood loss and number of blood transfusions in patients with hypocoagulation and hemorrhagic diathesis. However, the analysis of literature data shows that the drugs applied for the control of bleeding, traditionally used in medical practice, are not effective enough. This study deals with the systemic hemostatic activity of bis (2-aminoethan-1- sulfonate) calcium in the experiment. Methods: Experimental work in vitro is performed on the blood of healthy male donors, under conditions in vivo it is done on intraperitoneal injection in male rats. Thromboelastography was carried out with apparatus Thromboelastography (TEG) 5000 (Haemoscope Corporation, United States). The influence of first synthesized derivative and ethamsylate on functional activity of platelets was studied using a platelet aggregation analyzer Biola 230LAâ€ (Russia). Experimental evaluation of the system specific hemostatic activity in vivo was carried out using the model of parenchymatous bleeding in mature male rats. The interference came amid registration of bleeding stop time and extent of blood loss. Results: Bis (2-aminoethan-1-sulfonate) calcium shows procoagulation and proaggregant activity both in vitro and in vivo. Proaggregatory effect of bis (2-aminoethan-1-sulfonate) calcium is successfully implemented in the systemic hemostatic activity in terms of parenchymal bleeding, surpassing the control group and the group of etamsylate. Conclusion: The results of these studies reveal potentially high systemic hemostatic activity of bis (2-aminoethan-1-sulfonate) calcium, urging the need for further study on this compound and its analogs to create on their basis highly efficient, selective correctors of the hemostatic system.